Simulation of Heat Transfer Characteristics on Palm Oil as Electrical Insulating Material Using Finite Difference Method - Yanuar Z., Arief; Mohd. Shuffy, Suhaidi; Naemah, Mubarakah; May, Raksmey; Irza, Sukmana; Rosyid Ridlo, Al Hakim (2021)
The purpose of this research work is to study the heat transfer characteristics of palm oil as insulating material using finite difference method (FDM). Analysis and investigations of several heat transfer characteristics of palm oil were performed to determine the heat transfer performance of this oil. The characteristics obtained is then compared to other insulating oils to determine the performance of the insulating material. The simulation was done using Computational Fluid Dynamics (CFD) software that uses finite difference method concept that could perform 2D simulation to visualize the heat transfer characteristics inside the design of 2D transformer model geometry. The winding temperature is set into initial condition under full load temperature. The fluids properties of insulating material such as density, viscosity, thermal conductivity and specific heat capacity are set as constant, respectively. The simulation is set to constant running time of 30 minutes with interval of 5 minutes. The heat transfer characteristics such as fluid temperature, winding temperature, velocity profile, density and viscosity, heat flux from the winding and heat transfer characteristics are defined as variables, respectively. The results shows significant decrease of fluid and winding temperature of a transformer with palm oil as insulating material and has better heat transfer performance than other vegetative oils.